Activity Trends for the Selective Oxidation of 2-Propanol to Acetone on Noble Metal Electrodes in Alkaline Electrolyte - Mangoufis-Giasin, Iosif; Fusek, Lukáš; Yang, Tian; Khanipour, Peyman; Brummel, Olaf; Libuda, Jörg; Mayrhofer, Karl J.J.; Calle-Vallejo, Federico; Katsounaros, Ioannis (ACS Catalysis, 2023)
Fuel cells based on 2-propanol can be used to produce electricity utilizing the hydrogen stored in liquid organic hydrogen carriers. While the focus has previously been on acidic media, where only platinum-based electrodes are active, we explore here the oxidation of 2-propanol in alkaline solutions on different noble metal electrodes. Using experimental and computational methods, we find that the reaction is selective to acetone, whereas C-C bond breaking and the formation of adsorbed CO do not take place. The onset potential increases along the series Rh < Pt < Pd < Au, a trend that correlates with the adsorption energy of acetone on the respective surfaces. The oxidation rate decays under potentiostatic conditions due to the progressive accumulation of acetone at the surface. At high overpotentials, the reaction is limited by oxide formation. Given that alkaline systems are not restricted to exclusively platinum-based electrodes, a broader range of materials may be found that act as anodes for efficient 2-propanol fuel cells.
CRIS-Team Scopus Importer:2023-12-08
Keywords: acetone adsorption energy; alcohol fuel cells; alkaline media; fuel cell anodes; hydrogen economy; isopropanol oxidation; liquid organic hydrogen carriers; volcano plot

Anchoring of porphyrins on atomically defined cobalt oxide: In-situ infrared spectroscopy at the electrified solid/liquid interface - Fusek, Lukáš; Kastenmeier, Maximilian; Franz, Evanie; Fromm, Lukas; Görling, Andreas; Brummel, Olaf; Libuda, Jörg (Surface Science, 2022)
In this work, we studied the interaction of 5-mono(4-phosphonatophenyl)-10–15–20-(triphenyl) porphyrin (MPTPP) with an atomically-defined Co3O4(111) surface in electrochemical environments. We prepared clean and well-defined Co3O4(111) films by physical vapor deposition in ultra-high vacuum (UHV) and transferred the samples into liquid environment without exposure to ambient conditions. We anchored MPTPP to Co3O4(111) in the liquid phase using two different solvents, namely ethanol and dichloromethane. After a second transfer step into an aqueous electrolyte (0.15 M ammonia buffer, pH 10), we investigated the interaction of the porphyrin with the oxide surface in a potential window from 0.3 to 1.3 VRHE using electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We observed that MPTPP binds via the phosphonate group to the Co2+ surface ions in the form of chelating tridentate. The binding motif remains unchanged in the entire potential region studied. While the binding motif was independent of the solvent used for anchoring, a higher coverage of anchored porphyrins was observed when adsorbing from ethanol.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Electrochemistry; Infrared reflection absorption spectroscopy; Liquid phase; Organic/inorganic hybrid materials; Phosphonates; Ultra-high vacuum

Atomistic picture of electronic metal support interaction and the role of water - Fusek, Lukáš; Farnesi Camellone, Matteo; Ronovský, Michal; Kastenmeier, Maximilian; Skála, Tomáš; Kumar Samal, Pankaj; Tsud, Nataliya; Mehl, Sascha; Škvára, Jan; Dolák, Tomáš; Uvarov, Vitalii; Setvín, Martin; et al. (Journal of Materials Chemistry A, 2024)
Single atom catalysis (SAC) represents an emerging area of heterogeneous catalysis but faces challenges related to the low density of active sites and poor thermal stability. In this work, we present new fundamental insights into the nature of electronic metal support interactions (EMSI) coupled with cation exchange, which yield high density of atomically dispersed noble metals on defect-free terraces of cation-terminated reducible oxides. On well-ordered Co3O4(111) films, the mechanism involves temperature-controlled substitution of surface Co2+ and sub-surface Co3+ cations by Pt2+ and Pt4+ species, respectively. The cation exchange with Co2+ is coupled with the partial reduction of Co3O4(111), while the cation exchange with Co3+ involves the charge disproportionation within the Pt species. In the presence of co-adsorbed water, the Pt4+ species are stabilized at the surface in the form of triaqua complexes.
CRIS-Team Scopus Importer:2024-02-09

A Versatile Approach to Electrochemical in Situ Ambient-Pressure X-ray Photoelectron Spectroscopy: Application to a Complex Model Catalyst - Brummel, Olaf; Lykhach, Yaroslava; Ralaiarisoa, Maryline; Berasategui, Matias; Kastenmeier, Maximilian; Fusek, Lukáš; Simanenko, Alexander; Gu, Wenqing; Clark, Pip C. J.; Yivlialin, Rossella; Sear, Michael J.; Myslivecek, Josef; et al. (Journal of Physical Chemistry Letters, 2022)
We present a new technique for investigating complex model electrocatalysts by means of electrochemical in situ ambient-pressure X-ray photoelectron spectroscopy (AP-XPS). Using a specially designed miniature capillary device, we prepared a three-electrode electrochemical cell in a thin-layer configuration and analyzed the active electrode/electrolyte interface by using "tender"X-ray synchrotron radiation. We demonstrate the potential of this versatile method by investigating a complex model electrocatalyst. Specifically, we monitored the oxidation state of Pd nanoparticles supported on an ordered Co3O4(111) film on Ir(100) in an alkaline electrolyte under potential control. We found that the Pd oxide formed in the in situ experiment differs drastically from the one observed in an ex situ emersion experiment at similar potential. We attribute these differences to the decomposition of a labile palladium oxide/hydroxide species after emersion. Our experiment demonstrates the potential of our approach and the importance of electrochemical in situ AP-XPS for studying complex electrocatalytic interfaces.
CRIS-Team Scopus Importer:2022-12-16

Bimetallic Pd-Rh Nanoparticles Supported on Co3O4(111): Atomic Ordering and Stability - Simanenko, Alexander; Škvára, Jan; Samal, Pankaj Kumar; Fusek, Lukáš; Kastenmeier, Maximilian; Ronovský, Michal; Skála, Tomáš; Tsud, Nataliya; Mehl, Sascha; Johánek, Viktor; Mysliveček, Josef; Brummel, Olaf; et al. (Journal of Physical Chemistry C, 2025)
We have investigated the atomic ordering and stability of monometallic Rh and Pd nanoparticles and bimetallic Pd@Rh and Rh@Pd core@shell nanoparticles supported on well-ordered Co3O4(111) films on Ir(100) by means of synchrotron radiation photoelectron spectroscopy and scanning tunneling microscopy. The thermal stabilities of these model systems are controlled by the electronic metal support interaction associated with charge transfer at the metal/oxide interface. This effect is most pronounced in the Rh/Co3O4(111) model system. It is associated with the formation of atomically dispersed Rh3+ species at the metal/oxide interface and the growth of highly dispersed Rh nanoparticles. The system is stable up to 450 K. Annealing of the Rh/Co3O4(111) model system triggers sintering of the Rh nanoparticles above 450 K and Rh dissolution into the Co3O4(111) substrate above 550 K. The morphologies of the Pd@Rh and Rh@Pd core@shell nanoparticles are similar to those observed for the Rh/Co3O4(111) model system. With respect to atomic ordering, the Rh@Pd core@shell nanoparticles are fairly stable, while segregation of Pd in the Pd@Rh core@shell nanoparticles occurs upon annealing to 550 K. Above 550 K, redistribution of the charge at the metal/oxide interface leads to sintering, dissolution of Rh into the Co3O4(111) substrate and collapse of the core@shell nanoparticles. In particular, phase separation in the Pd@Rh and Rh@Pd core@shell nanoparticles occurs upon annealing above 550 K, yielding Rh-rich and Pd-rich nanoparticles on Co3O4(111).
CRIS-Team Scopus Importer:2025-01-31

Electrochemically Triggered Energy Release from an Azothiophene-Based Molecular Solar Thermal System - Franz, Evanie; Kunz, Anne; Oberhof, Nils; Heindl, Andreas H.; Bertram, Manon; Fusek, Lukáš; Taccardi, Nicola; Wasserscheid, Peter; Dreuw, Andreas; Wegner, Hermann A.; Brummel, Olaf; Libuda, Jörg (Chemsuschem, 2022)
Molecular solar thermal (MOST) systems combine solar energy conversion, storage, and release in simple one-photon one-molecule processes. Here, we address the electrochemically triggered energy release from an azothiophene-based MOST system by photoelectrochemical infrared reflection absorption spectroscopy (PEC-IRRAS) and density functional theory (DFT). Specifically, the electrochemically triggered back-reaction from the energy rich (Z)-3-cyanophenylazothiophene to its energy lean (E)-isomer using highly oriented pyrolytic graphite (HOPG) as the working electrode was studied. Theory predicts that two reaction channels are accessible, an oxidative one (hole-catalyzed) and a reductive one (electron-catalyzed). Experimentally it was found that the photo-isomer decomposes during hole-catalyzed energy release. Electrochemically triggered back-conversion was possible, however, through the electron-catalyzed reaction channel. The reaction rate could be tuned by the electrode potential within two orders of magnitude. It was shown that the MOST system withstands 100 conversion cycles without detectable decomposition of the photoswitch. After 100 cycles, the photochemical conversion was still quantitative and the electrochemically triggered back-reaction reached 94 % of the original conversion level.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Electrochemistry; Energy Storage; Photochemistry; Photoswitches; Solar Thermal Fuels

Particle Size and Shape Effects in Electrochemical Environments: Pd Particles Supported on Ordered Co3O4(111) and Highly Oriented Pyrolytic Graphite - Kastenmeier, Maximilian; Fusek, Lukáš; Deng, Xin; Skala, Tomas; Mehl, Sascha; Tsud, Nataliya; Grau, Sebastian; Stumm, Corinna; Uvarov, Vitalii; Johanek, Viktor; Libuda, Jörg; Lykhach, Yaroslava; et al. (Journal of Physical Chemistry C, 2022)
Particle size and shape effects control the oxidation behavior of nanostructured electrocatalysts. We investigated the oxidation state of Pd nanoparticles supported on Ar+-sputtered highly oriented pyrolytic graphite (HOPG) and well-ordered Co3O4(111) films on Ir(100) as a function of electrode potential by means of synchrotron radiation photoelectron spectroscopy coupled with an ex situ emersion electrochemical (EC) cell. Scanning tunneling microscopy revealed the growth of hemispherical and flat Pd nanoparticles on Ar+-sputtered HOPG and Co3O4(111), respectively. The oxidation state of Pd nanoparticles is controlled by electronic metal support interaction (EMSI) associated with charge transfer at the interface. We found that the Pd nanoparticles are largely metallic on HOPG and partially oxidized on Co3O4(111). Specifically, we detected the formation of partially oxidized Pdδ+aggregates in combination with atomically dispersed Pd2+species. The latter species dominate at small Pd coverage and form the metal/oxide interface at high Pd coverage. Immersion into an alkaline electrolyte (pH 10, phosphate buffer) at potentials between 0.5 and 1.1 VRHEhas no significant effect for Pd/Co3O4(111) but yields traces of surface Pd oxide at 0.9 and 1.1 VRHEfor Pd/HOPG. Formation of PdO was observed at 1.3 and 1.5 VRHE. Quantitative analysis suggests nearly one monolayer and nearly two monolayers of PdO on the surfaces of the Pd nanoparticles supported on HOPG and Co3O4(111) at 1.5 VRHE, respectively. The differences in the oxidation behavior reveal the decisive role of the EMSI in the stability of the metal/oxide interfaces in an EC environment.
CRIS-Team Scopus Importer:2022-09-02

Pd/Co3O4(111) Interface Formation - Kastenmeier, Maximilian; Fusek, Lukáš; Mohamed, Fatema; Schuschke, Christian; Ronovský, Michal; Skála, Tomáš; Farnesi Camellone, Matteo; Tsud, Nataliya; Johánek, Viktor; Fabris, Stefano; Libuda, Jörg; Piccinin, Simone; et al. (Journal of Physical Chemistry C, 2023)
The formation of the metal-oxide interface in the Pd/Co3O4(111) model catalyst was investigated by means of density functional theory (DFT), synchrotron radiation photoelectron spectroscopy (SRPES), and scanning tunneling microscopy (STM). The electronic metal-support interaction results in a substantial charge transfer at the interface yielding atomically dispersed Pd2+ species and partially oxidized Pdδ+ aggregates coupled with a partial reduction of Co3O4(111). Atomically dispersed Pd2+ species at the fcc site on the Co3O4(111) surface were found to be the most energetically favorable configuration. In comparison to the dispersed Pd2+ species, the formation of Pd dimers, trimers, and tetramers was found to be less favorable. The analysis of the Bader charges revealed a substantial net positive charge on Pd atoms in dimers, trimers, and tetramers which is consistent with the formation of partially oxidized Pdδ+ aggregates detected by SRPES. The analysis of the charge distribution in Co3O4(111) revealed a partial reduction of Co3+ to Co2+ cations in the first and second Co layers. According to DFT, Pdδ+ aggregates are prone to oxidation to PdO in the presence of O2 and H2O. The partially oxidized Pdδ+ and Pd4Ox aggregates form 1 to 2 monolayer thick clusters which serve as nuclei for the growth of metallic Pd0 nanoparticles. At high Pd coverage, Pd nanoparticles coalesce resulting in the growth of two-dimensional islands that densely cover the Co3O4(111) substrate.
CRIS-Team Scopus Importer:2023-03-29

Stability of the Pd/Co3O4(111) Model Catalysts in Oxidizing and Humid Environments - Schuschke, Christian; Fusek, Lukáš; Uvarov, Vitalii; Vorokhta, Mykhailo; Smid, Bretislav; Johanek, Viktor; Lykhach, Yaroslava; Libuda, Jörg; Myslivecek, Josef; Brummel, Olaf (Journal of Physical Chemistry C, 2021)
The oxidation state and stability of Pd nanoparticles supported on well-ordered Co3O4(111) films prepared on Ir(100) have been investigated in UHV and under both oxidizing and humid conditions by means of scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and near ambient X-ray photoelectron spectroscopy (NAP-XPS). After preparation, the supported Pd nanoparticles (size 4 nm) were found to be predominantly metallic. Small amounts of Pd2+, resulting from the electronic metal support interaction (EMSI), were found in the form of PdO and as ionic species dissolved in Co3O4(111). Annealing of the Pd/Co3O4(111) model catalyst in UHV triggers sintering of the Pd nanoparticles but leaves the oxidation states of Pd and the substrate largely unaffected. The oxidation of Pd/Co3O4(111) is coupled with dissolution of Pd2+ species into Co3O4(111) and underlying Ir(100) resulting in a significant loss of Pd from the surface. The corresponding phenomenon occurs largely under oxidizing and, to a minor extent, under humid conditions. The reverse oxygen spillover is facilitated in the presence of Pd2+ species dissolved in Co3O4(111) yielding Pd nanoparticles supported on CoO(111). The CoO(111) support remains stable under humid conditions but is reversibly converted to Co3O4(111) under oxidizing conditions.
CRIS-Team WoS Importer:2021-03-12

Toward High-Energy-Density Fuels for Direct Liquid Organic Hydrogen Carrier Fuel Cells: Electrooxidation of 1-Cyclohexylethanol - Fusek, Lukáš; Briega-Martos, Valentín; Minichová, Maria; Fromm, Lukas; Franz, Evanie; Yang, Juntao; Görling, Andreas; Mayrhofer, Karl J.J.; Wasserscheid, Peter; Cherevko, Serhiy; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry Letters, 2024)
Electrochemically active liquid organic hydrogen carriers (EC-LOHCs) can be used directly in fuel cells; so far, however, they have rather low hydrogen storage capacities. In this work, we study the electrooxidation of a potential EC-LOHC with increased energy density, 1-cyclohexylethanol, which consists of two storage functionalities (a secondary alcohol and a cyclohexyl group). We investigated the product spectrum on low-index Pt single-crystal surfaces in an acidic environment by combining cyclic voltammetry, chronoamperometry, and in situ infrared spectroscopy, supported by density functional theory. We show that the electrooxidation of 1-cyclohexylethanol is a highly structure-sensitive reaction with activities Pt(111) ≫ Pt(100) > Pt(110). Most importantly, we demonstrate that 1-cyclohexylethanol can be directly converted to acetophenone, which desorbs from the electrode surface. However, decomposition products are formed, which lead to poisoning. If the latter side reactions could be suppressed, the electrooxidation of 1-cyclohexylethanol would enable the development of EC-LOHCs with greatly increased hydrogen storage capacities.
CRIS-Team Scopus Importer:2024-03-15